The impact of COVID-19 pandemic on family caregivers' mental health: a rapid systematic review of the current evidence: COVID-19 and family caregivers' mental health - Dellafiore, Federica; Arrigoni, Cristina; NANIA, Tiziana; Caruso, Rosario; Baroni, Irene; Vangone, Ida; Russo, Sara; Barello, Serena (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of the work. Older adults, especially in isolation and with cognitive decline/dementia, can become more anxious and stressed during the quarantine. All these symptoms negatively affect the psycho-physical health of their caregivers. This study aimed to synthesize the current evidence on the impact of the COVID-19 pandemic on caregivers' mental health. Methods. A rapid systematic review was conducted using the following databases: Pubmed/Medline, CINAHL, Scopus, and PsycInfo (PROSPERO registration number: CRD42020215485). The ‘PRISMA’ flow chart guided the selection of articles. The search was entirely performed up to September 15th, 2021. Results. The narrative synthesis has brought out two main themes that represent the current debate in literature: "Family caregivers COVID-19 related stress", and "(Mal)adaptive strategies to the "new" normality". Conclusions. This study provides an evidence synthesis of the negative mental health impact experienced by caregivers of older adults during the COVID-19 pandemic.